Pengaruh digitalisasi pembelajaran bahasa, sastra, dan budaya mandarin - Ilmassafa, Azmy Zainur Rahma; Putri, Enty Prettycia; Sunarti, Sunarti (Fakultas Sastra Universitas Negeri Malang, 2022)
An example of the development in our education system is the application of technology-based learning lately. One of the educational focuses that are directly affected by the digitalization era is the study of Mandarin language, culture, and literature. The method used in this article is a descriptive qualitative method. By reviewing the previous studies on this matter, the purpose of this conceptual article is to study the changes that have occurred in the digitalization era, especially in the process of learning the Chinese language, culture, and literature. This article reveals that digitalization brings both negative and positive impacts. The positive impacts of digitalization learning include learning flexibility, ease of access to learning, and increased interest in learning the Mandarin language and culture. Meanwhile, the negative impact includes a lack of honesty in learning, lack of focus during learning, and lack of supervision from educators.